Prevalence, haemolysis and antibiograms of Campylobacters isolated from pigs from three farm settlements in Venda region, Limpopo province, South Africa - P. O. Uaboi-Egbenni; P. O. Bessong; A. Samie; C. L. Obi (African Journal of Pig Farming, 2018)
We investigated the prevalence, haemolytic activities and antibiotic susceptibility profiles of Campylobacter species isolated from pigs in three farms in the Venda region, Limpopo province, South Africa. During the period of investigation, which spanned over one year, 450 faeces samples from pigs comprising 150 each from the three farms were collected and appropriately transported to the base laboratory at the Department of Microbiology, University of Venda for analysis. In total, the prevalence rate of Campylobacter isolates from all three farms was 30.2%, whereas, the rates of 25 - 26% were recorded for farms X, Y and Z, respectively. Out of the isolated Campylobacter species 10 (12.5%) were identified as Campylobacter jejuni and 70(87.5%) as Campylobacter coli. Of the Campylobacter isolates from the farms, 23, 22 and 35 were β-haemolytic from farms X, Y and Z, respectively. Susceptibility of the isolates to 12 antibiotics was determined by disc diffusion technique. The overall rate of resistance determined in this study to most of the antibiotics was 84.2%. Most Campylobacter isolates from farm X (< 50%) were resistant to ciprofloxacin, cefexime, and erythromycin, while > 50% were resistant to tetracycline, (54.5%) to vancomycin, (100%) to ampicillin and methicillin. The rates of resistance to these antibiotics were not significantly different from farms X and Y (p < 0.005). However, most isolates from farm Y were more resistant to ciprofloxacin (57.1%) than isolates from farm X (36.4%) and Z (40.7%). Resistance rates to tetracycline by C. coli isolated from farm Y (48%), farm Z (45.5%) and farm X (44.4%) were noted. Similar trend was observed for C. coli from farm Y (40%), farm Z (31.8%) and farm X (22.2%) for ciprofloxacin. All C. coli from farm Z showed higher level of resistance to ampicillin (100%), Y (64%) and X (55.6%). The C. jejuni isolates though few were markedly resistant to fluoroquinolone and the macrolide as well as aminoglycoside antibiotics. Most of the isolates were resistant to at least seven (7) of the antibiotics tested. These observations indicate high levels of resistance to antibiotics commonly used in the swine industry (erythromycin and tetracycline) among the C. coli and C. jejuni isolates from pigs. Erythromycin and ciprofloxacin are drugs for treatment of human campylobacteriosis. The high prevalence rate of resistance to these drugs among C. coli and C. jejuni isolates from pig faeces is of public health significance.